2020
DOI: 10.1007/s00018-020-03693-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging cellular and molecular determinants of idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF), the most common form of idiopathic interstitial pneumonia, is a progressive, irreversible, and typically lethal disease characterized by an abnormal fibrotic response involving vast areas of the lungs. Given the poor knowledge of the mechanisms underpinning IPF onset and progression, a better understanding of the cellular processes and molecular pathways involved is essential for the development of effective therapies, currently lacking. Besides a number of established IPF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
152
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(173 citation statements)
references
References 331 publications
2
152
0
3
Order By: Relevance
“…Idiopathic pulmonary fibrosis (IPF) is a chronic progressive fibrotic lung disease wherein the distal lung tissue is mired in a perpetual wound response due, in part, to defective alveolar epithelial repair ( 1 , 2 ). Various influences contribute to chronic epithelial dysfunction, including genetic factors, age, and exposure to environmental insults including cigarette smoke and viral infection ( 3 , 4 ). Deficits in alveolar epithelial integrity result in compromised gas exchange, barrier dysfunction, inflammation, and excessive deposition of extracellular matrix leading to fibrosis and destruction of lung parenchyma ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is a chronic progressive fibrotic lung disease wherein the distal lung tissue is mired in a perpetual wound response due, in part, to defective alveolar epithelial repair ( 1 , 2 ). Various influences contribute to chronic epithelial dysfunction, including genetic factors, age, and exposure to environmental insults including cigarette smoke and viral infection ( 3 , 4 ). Deficits in alveolar epithelial integrity result in compromised gas exchange, barrier dysfunction, inflammation, and excessive deposition of extracellular matrix leading to fibrosis and destruction of lung parenchyma ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, concurrently with the loss of typical endothelial markers, such as vascular endothelial cadherin (VE-cadherin), platelet endothelial cell adhesion molecule (PECAM-1), also known as CD31, and von Willebrand Factor (vWF), they acquire the ability to express several mesenchymal markers, such as alpha-smooth muscle actin (α-SMA), smooth muscle protein 22 alpha (SM22α), fibronectin, vimentin, and fibroblast specific protein-1 (FSP-1) ( Dejana et al, 2017 ; Hong et al, 2018 ). EndMT is involved in many chronic and fibrotic disease states and appears to be regulated by several factors ( Evrard et al, 2016 ; Thuan et al, 2018 ; Phan et al, 2020 ). In diabetes, oxidative stress is emerging as an important trigger of the ECs transformation into myofibroblasts and vascular remodeling ( Montorfano et al, 2014 ; Thuan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lower body mass index (BMI) and body weight loss seemed to be related to poor outcomes [40]. Altogether, the convergence of genetic and phenotype-level results suggested that metabolic dysregulation might be a critical contributor to the pathogenesis of IPF [41]. Notably, many top correlated phenotypes such as BMI, emphysema, FVC, monocytes, albumin, and neutrophilia appeared to be key IPF survival predictors or clinical markers [42].…”
Section: Discussionmentioning
confidence: 99%